Covid 19 and beyond: a procedure for HVAC systems to address infectious aerosol illness transmission - Douglas Stuart Walkinshaw; Raymond Henry Horstman (Frontiers in Built Environment)
From pandemic to seasonal, the COVID-19 pandemic experience suggests many common respiratory infections rather than likely having a fomite etiology as previously thought, are primarily caused by the inhalation of infectious aerosols shed by ill persons during coughing and normal breathing and talking. Given this new understanding, the good news is that, unlike indoor-sourced noxious and irritating gases that can only be mitigated practically by diluting them with outdoor air ventilation, the indoor infectious aerosol illness transmission route can be addressed by circulating already conditioned air through commonplace commercial filters. Given that infectious aerosols released from the breath of occupants were practically an unknown vector of respiratory disease in the healthcare community for many decades, understandably HVAC regulations have not addressed this issue yet. However, this is about to change. To further this new end, this paper develops the formulae needed to set conditioned air recirculation rates through such filters for design infectious aerosol emission and inhalation rates, HID values, exposure times and occupancies, and target significantly lower than currently normal airborne infection reproduction rates. The analysis extends the equations previously developed for group inhalation of infectious aerosols to develop equations predicting the number of infections likely to occur from this inhalation and the rate of disease spread (reproduction). The governing equations provided and exemplified use group exposures since the number of infections (reproduction number) is group based. Examples using the equations provided are given for many different settings and two case study findings are compared with their predictions. Some settings such as the typical office are shown to already have a relatively low infection reproduction rate. Alternatively, others such as a typical school classroom or a longer commercial air flight require increased filtered ventilation air flows to yield a similarly low reproduction rate. The formulae and their application will be of interest to government and industry health and HVAC standard setting bodies.